To Assess Effect of Smoking on Cerebral Blood Flow - Akanksha Sisodia (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Smoking is known to interfere with NO mediated endothelial function therefore impairing the cerebrovascular blood flow (CBF).Cigarette smokers also have raised fibrinogen levels and platelet count which makes the blood stickier. All these factors make smokers more vulnerable to cerebrovascular diseases. Purpose of the Study The purpose of the present study was to determine whether the level of cigarette use is a significant predictor CBF when age, gender, is controlled. The objective of the study was to assess and compare cerebral blood flow in smokers and non- smokers and to correlate the alterations in cerebral blood flow with the no. of cigarettes and duration of smoking. Methods The subjects consisted of 50 smokers and 50 non-smokers without any history of respiratory disease, cardiac disease or any other chronic disease. Smoking index was calculated and Mean cerebral blood flow (CBF) in Anterior (ACA), Middle (MCA) & Posterior (PCA) cerebral arteries were measured by the Trans-cranial Doppler method (TCD) method. Results Subjects had an average smoking index of (number of cigarette smoked per day) x year of smoking history) 450 +_ 164. CBF was measured using trans-cranial Doppler method. Simple linear regression analysis demonstrated a negative correlation of smoking index with CBF in all the major cerebral arteries (LMCA, r = -0.119), (RMCA, r = -0.34), (LACA, r = -0.36),( RACA, r = -0.34),(LPCA, r = -0.33) and (RPCA, r= .000).